SPIRITUALITY TO UNDERSTAND PLURALITY: DIASPORA PATH TO GOD - Salamuddin, Salamuddin; Rambe, Elismayanti (Peminat Ilmu Ushuluddin, 2024)
This article aims to explain the meaning of spirituality which is then linked to the plurality of religions, both of which intersect and are interconnected. The connection between the two becomes a way to understand that natural reality is created by the law of plurality, multi-variety. The consequence of this diversity, more specifically in religion, is that it gives rise to a real plurality of teachings, values, understandings and differences, which are not only different but also conflict with one another. Thus, each religious follower understands plurality as a path to God. It can be concluded that by using spirituality glasses to see plurality, the perspective on and for ' the others' does not clash one religion with another religion from any aspect. Religious competition no longer seeks to increase the 'quantity' of the number of adherents, but rather increases the 'quality' of output from each religious teaching.